Bioactive poly(ethylene glycol) hydrogels to recapitulate the HSC niche and facilitate HSC expansion in culture. Issue 4 (26th October 2015) - Cuchiara, Maude L.; Coşkun, Süleyman; Banda, Omar A.; Horter, Kelsey L.; Hirschi, Karen K.; West, Jennifer L.
ABSTRACT: Hematopoietic stem cells (HSCs) have been used therapeutically for decades, yet their widespread clinical use is hampered by the inability to expand HSCs successfully in vitro. In culture, HSCs rapidly differentiate and lose their ability to self‐renew. We hypothesize that by mimicking aspects of the bone marrow microenvironment in vitro we can better control the expansion and differentiation of these cells. In this work, derivatives of poly(ethylene glycol) diacrylate hydrogels were used as a culture substrate for hematopoietic stem and progenitor cell (HSPC) populations. Key HSC cytokines, stem cell factor (SCF) and interferon‐γ (IFNγ), as well as the cell adhesion ligands RGDS and connecting segment 1 were covalently immobilized onto the surface of the hydrogels. With the use of SCF and IFNγ, we observed significant expansion of HSPCs, ∼97 and ∼104 fold respectively, while maintaining c‐kit + lin − and c‐kit + Sca1 + lin − (KSL) populations and the ability to form multilineage colonies after 14 days. HSPCs were also encapsulated within degradable poly(ethylene glycol) hydrogels for three‐dimensional culture. After expansion in hydrogels, ∼60% of cells were c‐kit +, demonstrating no loss in the proportion of these cells over the 14 day culture period, and ∼50% of colonies formed were multilineage, indicating that the cells retained their differentiation potential. The ability to tailor and use this system to support HSC growth could have implications on the future use of HSCs and other blood cell types in a clinical setting. Biotechnol. Bioeng. 2016;113: 870–881. © 2015 Wiley Periodicals, Inc. Abstract : Primary hematopoietic cells were isolated and cultured for two weeks in poly(ethylene glycol) hydrogel wells and within protease degradable poly(ethylene glycol) hydrogels. The hydrogel materials were covalently functionalized with peptides (RGDS, CS1) and proteins (SCF, IFNγ) found in the native hematopoietic stem cell (HSC) microenvironment. During the culture period, cells proliferated significantly while maintaining their ability to differentiate down multiple hematopoietic lineages, suggesting the ability of this system to support the expansion of clinically relevant HSC populations.